Danger in the darkest hour - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series., 2015)
"The magic tree house has taken Jack and Annie back in time to England in 1944. England is fighting for its life in World War II. Before long, Jack and Annie find themselves parachuting into Normandy, France, behind enemy lines. The date is June 5. Will the brave brother and sister team be able to make a difference during one of the darkest times in history?"--